1. A particle moves on the x-axis. It's displacement, x m, from the origin O is given by: x = 3t2 - 3t + 2, where t is the time in seconds.
How far is the particle from O when it is instantaneously at rest?
~~
2. In this question, i and j are the standard unit vectors in the Ox and Oy directions.
An object has initial position (2i - j)m and velocity (-i + 4j)ms-1. It has a costant acceleration of (2i + 5j)ms-2.
Calculate the object's velocity and position after four seconds.
~~
3. A racing car starts off down a straight section of the track towards the first corner. Its speed, vms-1, is modelled for the first four seconds of its motion by: v = t3 - 9t2 + 24t, 0 < t < 4.
Find an expression for the distance travelled by the car in the first t seconds.
~~
4. The position vector, r, of a particle at time t is given by: r = t2 + (5t - 2t2)j, where i and j are the standard unit vectors, lengths are in metres and time is in seconds.
Find an expression for the acceleration of the particle.
"Q1. A particle moves on the x-axis. It's displacement, x m, from the origin O is given by: x = 3t^2 - 3t + 2, where t is the time in seconds.
How far is the particle from O when it is instantaneously at rest?"
dx/dt = 6t - 3 = 0 --> t = 1/2 x = 3(1/2)^2 - 3(1/2) + 2 = 5/4m
"3. A racing car starts off down a straight section of the track towards the first corner. Its speed, vms-1, is modelled for the first four seconds of its motion by: v = t^3 - 9t^2 + 24t, 0 < t < 4.
Find an expression for the distance travelled by the car in the first t seconds."
s = integral of v s = (t^4)/4 - 3t^3 + 12t^2 + c at s=0, t=0 0 = c s = (t^4)/4 - 3t^3 + 12t^2
I'll see if i can come up with anything for the vectors, but don't get too hopeful on that
4. The position vector, r, of a particle at time t is given by: r = t^2 i + (5t - 2t^2)j, where i and j are the standard unit vectors, lengths are in metres and time is in seconds.
Find an expression for the acceleration of the particle.
I think you just have to differentiate twice to get acceleration.
r = t^2 i + (5t - 2t^2) j v = 2t i + (5 - 4t) j a = 2 i - 4 j